The serpent's shadow - Riordan, Rick.; Gengaro, Michelle (New York : Disney/Hyperion Books, 2012)
When Apophis, the chaos snake, threatens to plunge the world into eternal darkness, siblings Carter and Sade Kane plan to use an ancient spell to destroy the snake, but first must rely on the murderous ghost of a powerful magician.
4.9
5-8
Keywords: Voyages and travels -- Juvenile fiction; Mythology, Egyptian -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Secrecy -- Juvenile fiction; Voyages and travels -- Fiction; Mythology, Egyptian -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Secrets -- Fiction; Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Egyptian mythology -- Fiction; Magic -- Fiction; Siblings -- Fiction; Secrecy -- Fiction; Adventure fiction; Adventure fiction